2003
DOI: 10.7547/87507315-93-1-27
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of High-Heeled Gait

Abstract: A within-subject comparative study of walking while wearing low-heeled sports shoes versus high-heeled dress shoes was performed to identify and describe changes in lower-extremity joint kinetics associated with wearing high-heeled shoes during level overground walking. A volunteer sample of 15 unimpaired female subjects recruited from the local community underwent quantitative measurement of sagittal and frontal plane lower-extremity joint function, including angular motion, muscular moment, power, and work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
103
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 11 publications
13
103
1
4
Order By: Relevance
“…Higher peak plantar pressures are associated with increased pain and discomfort in the foot [10,15]. Therefore, there is a need to further evaluate and study such interactions of confounding variables that lead to increased forefoot loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher peak plantar pressures are associated with increased pain and discomfort in the foot [10,15]. Therefore, there is a need to further evaluate and study such interactions of confounding variables that lead to increased forefoot loading.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that high heeled shoes directly affect biomechanics of gait, including the peak plantar pressure distribution. There is an increase in peak plantar pressure under the forefoot as a result of realignment of body segment such that center of pressure shifts further anteriorly and medially [9,10,[15][16][17]. Speksnijder and colleagues report an increase of 30% in peak plantar pressure under the forefoot region in women wearing high heels [11].…”
Section: Introductionmentioning
confidence: 99%
“…28, [38][39][40] Following acclimatization, data were collected over a further 20 minutes at the same standardized speed. To minimize fatigue, each participant was allowed a 10 minute rest between each experimental condition and/or until their HR returned to its resting value.…”
Section: Methodsmentioning
confidence: 99%
“…This compensation may be carried out by means of postural changes developed over the time one wears these shoes 6,[9][10][11] . These changes were observed in some studies on trunk, knees, and ankles, and they do not follow a set of rules, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the habit of wearing high-heeled shoes must be highlighted, as it has become increasingly more common among teenagers from an earlier age [6][7][8][9][10][11] . Although high-heeled shoes are important accessories in women's apparel, the main concern is the improper wear which compromises the health of feet, legs, and spine 12 .…”
Section: Introductionmentioning
confidence: 99%